PENGARUH KOMPENSASI FINANSIAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU - Rosyia Wardani (Valid: Jurnal Ilmiah, 2016)
This study aims to determine a partial and simultan significant effect of financial compensation and discipline on teachers performances at the third vocational school of Mataram. The analysis determines to find a dominant influence on teachers performances too. This research is causal’s acociatif. A hundred populations have been select by cencus. Data collected by questionnaires. Instruments test have been used in this research by validity and reliability test. The analysis have been used by multiple regression analysis, simultan determinantion test (R2), t test, F test and standarized coeficients beta. The results showed that: (1) There is partial significant effect among financial compensation and discipline on teachers performances. (2) There is simultan significant effect among financial compensation and discipline on teachers performances. (3) Discipline has a dominant effect on teachers performances.